Robert Walser - Küppers, Almut; Surkamp, Carola (SCENARIO: Journal for Performative Teaching, Learning, Research, 2010)
A cage in the Berlin Zoo becomes a stage, and its resident lion an extremely impressive actor. Robert Walser wrote this text 100 years ago, fascinated by the animal’s mighty presence and its interplay with the audience. The text as well as Erika Fischer Lichte’s quote from the “Ästhetik des Performativen” below give an indication of the focus of this volume. “Presence is not an expressive but a purely performative quality. It is generated through specific processes of embodiment; the actor’s phenomenal body rules the space, demanding the audience’s attention.” [1] Very interesting is the Abyssinian Lion in the zoological gardens. He plays a tragedy and moreover in such a way that he simultaneously waxes and wanes. He despairs (nameless despair) and keeps himself nice and fat at the same time. He thrives and tortures himself to death all at once. And all this in front of a watching audience. I stood in front of his cage for a long time and couldn’t tear my eyes away from the royal drama. By the way, I would like to change my profession, if this could be done quickly and easily, and become a painter of animals. I could gorge myself on ...